(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Urban Cooperative Banks (UCBs) play a vital role in the financial ecosystem, particularly in urban areas where they serve as intermediaries for the underbanked and provide critical financial services to small businesses and individuals. This paper aims to evaluate the performance of UCBs in Lucknow District by assessing their financial stability, operational efficiency, and contribution to local economic development. Through both qualitative and quantitative analysis, including financial ratio analysis, customer surveys, and interviews with bank officials, this study provides an in-depth understanding of the current state of UCBs in Lucknow. The findings highlight strengths and areas for improvement in governance, credit management, technological adoption, and community engagement. The paper concludes with policy recommendations to enhance the performance and sustainability of UCBs in contributing to the broader economic and social development goals.